2020
DOI: 10.1183/23120541.00213-2020
|View full text |Cite
|
Sign up to set email alerts
|

Whole-exome sequencing accuracy in the diagnosis of primary ciliary dyskinesia

Abstract: The diagnosis of Primary Ciliary Dyskinesia (PCD) relies on clinical features and sophisticated studies. The detection of bi-allelic disease-causing variants confirms the diagnosis. However, a standardised genetic panel is not widely available and new disease-causing genes are continuously identified.To assess the accuracy of untargeted whole-exome sequencing (WES) as a diagnostic tool for PCD, patients with symptoms highly suggestive of PCD were consecutively included. Patients underwent measurement of nasal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 41 publications
1
11
1
Order By: Relevance
“…In Case 3, a patient with features of reduced generation of motile cilia and hydrocephalus, no pathogenic variants would been identified in a panel-based approach, even with targeted sequencing of potential candidates for known RGMC loci. The diagnostic rate of 100% in our small study is higher than previous reports, in which 60-70% of cases received a genetic diagnosis based on the known PCD gene panels (1,5,12,13,20), 75% on extended NGS panels (44) and 68-94% by WES (45)(46)(47)(48).…”
Section: Discussioncontrasting
confidence: 71%
“…In Case 3, a patient with features of reduced generation of motile cilia and hydrocephalus, no pathogenic variants would been identified in a panel-based approach, even with targeted sequencing of potential candidates for known RGMC loci. The diagnostic rate of 100% in our small study is higher than previous reports, in which 60-70% of cases received a genetic diagnosis based on the known PCD gene panels (1,5,12,13,20), 75% on extended NGS panels (44) and 68-94% by WES (45)(46)(47)(48).…”
Section: Discussioncontrasting
confidence: 71%
“…A study from Israel included predominantly Arab individuals and reported mutations in DNAH11 [ 38 ] to be the most common cause of PCD. A study of five children from two unrelated consanguineous Palestinian families revealed novel mutations in DNAAF11/LRRC6 (c.436G>C), which also affected families in this study [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Panels covering greater numbers of PCD genes will have greater detection rates [ 50 ] ( Figure 2 ). It is expected that the routine use of newer sequencing methods, such as whole exome sequencing (which offers better coverage), will likely replace panels with limited numbers of genes [ 51 ].…”
Section: Pcd Diagnostic Testingmentioning
confidence: 99%